Compostos fenólicos em uvas e vinhos da variedade Merlot - Fogaça, Aline de Oliveira (2012)
The main aim of this work was to evaluate the phenolic compounds of Merlot grapes and wines, from vineyards located at Dom Pedrito (Campanha Gaúcha) and Bento Gonçalves (Serra Gaúcha). The following aspects were evalueted: fenolic and industrial ripeness; correlation between the grapes phenolic potencial and the wine phenolics; changes in phenolic compounds during the aging of the wines; impacto of maceration time of wine phenolic composition. The study was conducted for three years: 2009, 2010 and 2011. After grape ripeness evaluations, grape samples were harvested, crushed and fermented , with three different maceration techniques. The phenolic composition of the wines were analyzed after bottling and during aging. The vineyard localization have a great influence on Merlot wine phenolic composition; the grape characteristics was most important than maceration techniques to the wine composition. Important differences, among this two regions, have been found in the content and in the composition of phenolic compounds in the grapes and wines. Dom Pedrito grapes achieved a good cellular maturity, however, when compared with Bento Gonçalves grapes, the anthocyanin content is lower and the quantity of seeds tannins are higher than 50%. The phenolic potential allowed to estimate the total phenolic content, color due polymeric anthocyanins and procyanidin content of Merlot wines. Extended maceration (15 days) are recommended to Dom Pedrito grapes, however it is observed an increase in the pH value; the total crushing of grapes or not will not influence this aspect. During the aging, the results are dependent of vineyard location; Dom Pedrito wines showed a greater polimerization velocity and the differences among maceration times decreased for all wines studied. The main differences among wines from this two regions were color intensity, anthocyanin content, color due polymeric anthocyanin and total phenolic conten of the wines. These facts allows to state that Merlot wines from Serra Gaúcha could be aging for a periodo greater than Campanha Gaúcha wines.